Pemahaman Siswa Terhadap Keliling Dan Luas Lingkaran - Puling Tang, Melki Imamastri (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2023)
Mathematics learning is a teaching and learning process built by teachers to develop students' creative thinking that can improve students' thinking skills, and can construct new knowledge as an effort to improve good mastery of mathematical material, especially around circles. The purpose of this study is how the knowledge of class VIII SMP Negeri Tamalabang on the value of phi (π) and the ability to understand and solve problems related to determining the circumference and circle. The research method used is descriptive qualitative. The form of descriptive research used is case research. The results showed that students' understanding in finding the value of phi and the formula for the circumference of a circle developed well from the comparison of pree test and post test. This learning design makes students look more active and begins to show the ability to express opinions even though the result is that there is a development in students' understanding. Students' understanding in finding the value of phi and the formula for the circumference and area of ​​a circle developed well from the comparison of pree test and post test. This learning design makes students look more active and begins to show the ability to express opinions even though the result is that there is a development in students' understanding. The average pree test and post test scores of 21 class VIII students of SMP Negeri Tamalabang are for the average pree test score for the area of ​​the circle is 55.05 and for the pree test average value is 84.76. Meanwhile, from the 21 people who were assessed, it turned out that the average value of the area of ​​the circle where the pree test score was 54,095 and the post test average was 86,190. This indicates that there is a well-developed understanding of the eighth grade students. In other words, many students understand the concept of the circumference of a circle and are able to solve problems related to the circumference of a circle. There needs to be motivation that stimulates students to continue to study hard, especially in the field of mathematics.